Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.pain.2013.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of multisite pain and associations with risk factors

Abstract: To explore definitions for multi-site pain, and compare associations with risk factors for different patterns of musculoskeletal pain, we analysed cross-sectional data from the Cultural and Psychosocial Influences on Disability (CUPID) study. The study sample comprised 12,410 adults aged 20-59 years from 47 occupational groups in 18 countries. A standardised questionnaire was used to collect information about pain in the past month at each of 10 anatomical sites, and about potential risk factors. Associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
142
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(178 citation statements)
references
References 25 publications
31
142
4
1
Order By: Relevance
“…8 Female sex, anxiety and depression, sleeping problems, smoking, overweight/obesity, and family history of pain are also known risk factors for chronic widespread pain (CWP). 3,32,45 Chronic musculoskeletal pain is complex and determined by multiple causal pathways involving biological, psychological, and social influences that can interact with each other.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…8 Female sex, anxiety and depression, sleeping problems, smoking, overweight/obesity, and family history of pain are also known risk factors for chronic widespread pain (CWP). 3,32,45 Chronic musculoskeletal pain is complex and determined by multiple causal pathways involving biological, psychological, and social influences that can interact with each other.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ordinal variables for anxiety and depression symptom load were computed as reference (0-4), sub-symptom load, (5-7) mild symptom load (8)(9)(10), moderate symptom load (11)(12)(13)(14), and severe symptom load (15)(16)(17)(18)(19)(20)(21). 4, 27 Sleeping problems were identified by two questions: "Have you had difficulty falling asleep in the last month?"…”
Section: Study Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the relationship extends to widespread pain [56], and there are indications that relative risks are even higher for pain occurring at multiple sites [10,12]. In particular, a large international study which compared associations with risk factors for different patterns of musculoskeletal pain, found that relative to no pain, pain that affected six or more anatomical sites showed a stronger association with tendency to somatise than pain involving fewer than four anatomical sites [57].Importantly, the relationship is not only with awareness and reporting of musculoskeletal symptoms, but also with disability for everyday activities as a consequence of musculoskeletal pain [10,[12][13][14]49].It is possible that the development of a musculoskeletal disorder could sensitise an individual to other symptoms. However, findings from longitudinal studies suggest that causation is in the reverse direction -i.e.…”
mentioning
confidence: 99%